Ответы и объяснения

2012-10-01T15:37:39+00:00

(m-n)^2+4mn            m^2-2mn+n^2+4mn             (m+n)^2

------------------=---------------------------------=---------------

 2mn(m-n)                       2mn(m-n)                       2mn(m-n)

 

 

 7p+q           p-7q       7p+q       7q-p            7pq+q^2+7pq-p^2    (q-p)(q+p)+14pq

-------- + ------------=--------  + -----------=-------------------------= --------------------

p(p-q)         q(q-p)      p(p-q)      q(p-q)          pq(p-q)                          pq(p-q)